2018
DOI: 10.1097/mao.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric Profiles in Patients With Normal Hearing and Bilateral or Unilateral Tinnitus

Abstract: The mechanism involved in the development of tinnitus may depend on its laterality. Bilateral tinnitus may be associated with hyperactivity at the level of the cochlear nucleus whereas a higher-order cortical area may be involved in unilateral tinnitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 20 publications
4
24
0
1
Order By: Relevance
“…According to Londero [11], tinnitus is often the only auditory sign associated with hearing loss and more than 80% of patients with tinnitus have an abnormal audiogram. This same finding was shared by Kudamo Song in South Korea and Betty in California [12] [13].…”
Section: Associated Signssupporting
confidence: 71%
“…According to Londero [11], tinnitus is often the only auditory sign associated with hearing loss and more than 80% of patients with tinnitus have an abnormal audiogram. This same finding was shared by Kudamo Song in South Korea and Betty in California [12] [13].…”
Section: Associated Signssupporting
confidence: 71%
“…Thus, the mechanism involved in the development of tinnitus may depend on its laterality [43]. Interestingly, it was also found that patients with unilateral tinnitus and normal hearing tended to have a higher THI score compared with bilateral tinnitus sufferers [43]. Tinnitus pitch, mean age of patients, and mean tinnitus duration were higher in the group with bilateral tinnitus [44].…”
Section: Discussionmentioning
confidence: 97%
“…They revealed the connection between bilateral tinnitus and hyperactivity at the level of the cochlear nucleus, as well as the involvement of the higher-order cortical area in unilateral tinnitus. Thus, the mechanism involved in the development of tinnitus may depend on its laterality [43]. Interestingly, it was also found that patients with unilateral tinnitus and normal hearing tended to have a higher THI score compared with bilateral tinnitus sufferers [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present case, tinnitus was not associated to clinically evident hearing loss; it has been previously reported that lesions affecting the auditory pathways may not determine an evident hearing loss in some cases 15 . Moreover, tinnitus and difficulties in speech perception, especially in noise, are often reported even in the absence of a clinically evident hearing loss 35,36 . Traditional theories assume that tinnitus is triggered by cochlear damage, mainly at the outer hair cell level; however, this would not apply to tinnitus patients presenting with a normal audiogram 36,37 .…”
Section: Audio-vestibular Alterations In Msmentioning
confidence: 99%